Greetings, wishes, toasts as a form of national character expression (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article is devoted to the study of structural features of the genre varieties paroemias (greetings, compliments, toast) from the point of view of their development in the national mentality and the reflection in them of fragments of national coloring. Identified means and techniques of expression of the national character of the Ukrainian people and the basic principles on which is founded the distinction of congratulations, wishes and toasts. Exploring such paroemia as greetings, wishes, toasts, we noticed that the subjects analyzed many of the works reflect the life of the Ukrainian people and their national traits: wealth, happiness, material prosperity.
Keywords: folklore; genre; greetings; wishes; toasts; paroemia; comparison; mentality; national character; olklore